Upaya pemenuhan kebutuhan sosial ekonomi penyandang disabilitas fisik studi pada DPD PPDI (Perkumpulan penyandang disabilitas indonesia) Jawa Barat: Study on the West Java Indonesian Association of People with Disabilities - Istiawati, Tari (Indonesian Journal of Social Work, 2023)
Humans have unlimited needs, which continue to increase over time, and people always try their best to meet those needs. Everything you want to have,, and enjoy is called a human need. Economic activity and social behavior disabled people are more likely to experience unfavorable socio-economic outcomes such as lack of education, worse health outcome, and lower employment rates. In the last decade, there has been progress in the rights of persons with disabilities, but people with disability and their families still face various challenges related to the socio-economic. purpose of this study To describe efforts to meet the social and economic needs of disabled persons, to describe the efforts to satisfy the socioeconomical needs of the disabled, The method used is to use a qualitative approach, which is done by studying the research descriptively/ The results of the research show that people with Disabilities can meet the needs of social and economics with a variety of creativity they have, of course, with the experiences that make the disability can rise and now can live in an environment that can always support in all conditions.Keywords: effots, disability, social and economic needs